Dynamic power decoupling for low-voltage ride-through of grid-forming inverters. (November 2022) - Ji, Feng; Xu, Zhuang; Gerada, C.
Abstract: In grid-forming technologies, the power controllers emulate the operation of synchronous generator. The frequency regulation, power-decoupling and virtual inertia are mostly achieved on the basis of small-signal models. However, the transient power and coupling mechanism of the converters have not been revealed thoroughly. If the voltage of grid-connection point drops because of power grid failure, it may lead to unbalance and instability for virtual synchronous generator (VSG). Normally, the active power is required to decrease to restrain the current and the reactive power is required to increase to support the voltage of the power grid during the fault. Therefore, the dynamic power decoupling is sensitive for the low-voltage ride-through (LVRT) for VSG. The traditional power decoupling control based on small signal models is not perfect for LVRT. In this paper, a graphical model is proposed for the analysis of transient power transfer and the reflection of the impact caused by the remarkable changes of the power angle and the grid voltage. The voltage compensation is designed to remedy the effect of power angle disturbance. The dynamic performance for LVRT can be improved by the control strategy based on large signals. The simulation and experiment results show that the suggested method is feasible.